Transformation of Risk Management HR in the Digital Age: Adaptation to Technology and Global Uncertainty - Yuliana, Lady; Madelin, Indah Lestari (Westscience Press, 2025)
The development of digital technology and increasing global uncertainty have prompted organizations to carry out a comprehensive transformation in the risk management system, especially in the aspect of human resources (HR). This study aims to examine how organizations transform risk management HR in response to the challenges of digitalization and the dynamics of an unstable global environment. The approach used is qualitative descriptive with data collection techniques through in-depth interviews, documentation studies, and limited observation on several public and private sector organizations that have implemented digital risk management systems. The results of the study show that human resource transformation in risk management includes three main aspects: (1) digital competency development, especially in the use of risk technology and data analysis; (2) restructuring the role and function of human resources from administrative to strategic; and (3) the formation of an organizational culture that is adaptive to risks and uncertainties. These findings confirm that the success of modern risk management systems depends not only on technological sophistication, but also on the readiness and ability of human resources to manage risk proactively and collaboratively. This research recommends that organizations place HR transformation as a strategic priority in strengthening risk management in the digital era, with a holistic and sustainable approach.